Critical Evaluation of Cross-Sectoral Collaborations to Inform the Implementation of the “One Health” Approach in Guadeloupe - Gruel, Gaëlle; Diouf, Mame Boucar; Abadie, Catherine; Chilin-Charles, Yolande; Etter, Eric Marcel Charles; Geffroy, Mariana; Herrmann Storck, Cécile; Meyer, Damien F.; Pagès, Nonito; Pressat, Gersende; Teycheney, Pierre-Yves; Umber, Marie; et al. (Frontiers in Public Health, 2021)
In Guadeloupe, a French overseas territory located in the Eastern Caribbean, infectious and non-infectious diseases, loss of biodiversity, natural disasters and global change threaten the health and well-being of animals, plants, and people. Implementing the “One Health” (OH) approach is crucial to reduce the archipelago's vulnerability to these health threats. However, OH remains underdeveloped in Guadeloupe, hampering efficient and effective intersectoral and transdisciplinary collaborations for disease surveillance and control. A multidisciplinary research group of volunteer researchers working in Guadeloupe, with collective expertise in infectious diseases, undertook a study to identify key attributes for OH operationalization by reviewing past and current local collaborative health initiatives and analyzing how much they mobilized the OH framework. The research group developed and applied an operational OH framework to assess critically collaborative initiatives addressing local health issues. Based on a literature review, a set of 13 opinion-based key criteria was defined. The criteria and associated scoring were measured through semi-directed interviews guided by a questionnaire to critically evaluate four initiatives in animal, human, plant, and environmental health research and epidemiological surveillance. Gaps, levers, and prospects were identified that will help health communities in Guadeloupe envision how to implement the OH approach to better address local health challenges. The methodology is simple, generic, and pragmatic and relies on existing resources. It can be transposed and adapted to other contexts to improve effectiveness and efficiency of OH initiatives, based on lessons-learned of local past or current multi-interdisciplinary and intersectoral initiatives.